PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN GREEN SCREEN BERBASIS ADOBE PREMIERE PRO PADA MATA KULIAH AUDIO VIDEO EDITING DI PROGRAM STUDI PENDIDIKAN TEKNIK ELEKTRO - Dede Nata Parwanta; I Nyoman Santiyadnya; I Putu Suka Arsa (Universitas Pendidikan Ganesha, 2021)
This study aims to create a green screen learning video based on Adobe Premiere Pro that is feasible to use and gets a good response from students in the audio video editing course in the Electrical Engineering Education undergraduate study program. This research uses research and development (R&D) methods. The data collection method used a questionnaire/questionnaire that was assessed by content experts, media experts, and students. The result of this research is the creation of a green screen learning video media based on Adobe Premiere Pro. Based on the results of the content expert test, 98% of the qualifications are very feasible, the media expert test results are 100% very qualified, and the test scores for small groups and large groups are 100% with very good qualifications. Based on the research results, green screen learning media based on Adobe Premiere Pro is feasible to use and gets a very good response from students in the audio-video editing course in the Undiksha Electrical Engineering Education S1 study program.